2008
DOI: 10.1002/ibd.20298
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in the use of immunomodulators and biologics for the treatment of inflammatory bowel disease: A retrospective cohort study

Abstract: There were trends toward lower odds of treatment with IFX or either 6-MP/AZA or IFX in AA when compared with Caucasians. Further studies are needed to determine if these differences are due to less severe disease in AA patients or due to disparities in care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 32 publications
4
33
0
Order By: Relevance
“…Furthermore, in addition to Black race being a predictor of higher utilization of emergency services, progressively lower household income was also a strong and independent factor. Our findings were consistent with those of Flasar et al who similarly found a lower frequency of steroid, immunomodulator, and infliximab use in Blacks (12). Disease activity may be an important predictor of immunomodulator and infliximab use, and chronic steroid use is considered by some as a surrogate indicator of disease severity.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, in addition to Black race being a predictor of higher utilization of emergency services, progressively lower household income was also a strong and independent factor. Our findings were consistent with those of Flasar et al who similarly found a lower frequency of steroid, immunomodulator, and infliximab use in Blacks (12). Disease activity may be an important predictor of immunomodulator and infliximab use, and chronic steroid use is considered by some as a surrogate indicator of disease severity.…”
Section: Discussionsupporting
confidence: 92%
“…This level of expenditure detail is especially important in a disease such as IBD where a wide range of services and treatments and associated costs exist, potentially revealing patterns that total expenditure figures alone fail to capture. 8,11,13 Using nationally representative data from 1996 to 2011, we determined that mean inpatient expenditures composed the highest proportion of IBD direct costs, above outpatient, emergency, office-based, and prescribed medicine costs. When IBD patients were stratified by insurance status, we found that publicly insured patients spent over double the mean expenditures of privately insured or uninsured patients, with differences of $10K and $13K, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Black patients utilized less ambulatory care, specialists, and biologics than whites, while exhibiting increased hospitalization rates. [10][11][12][13] Race-related health disparities have also been demonstrated in IBD disease phenotype, surgery rates, type of surgery, perianal fistulizing disease, and extraintestinal manifestations. 2,14 Lower income was associated with higher rates of CD-related surgery along with higher IBD-related hospitalizations, emergency department (ED) visits, and physician visits.…”
mentioning
confidence: 99%
“…Black patients utilized less ambulatory care, specialists, and biologics than whites, while exhibiting increased hospitalization rates. [10][11][12][13] Race-related health disparities have also been demonstrated in IBD disease phenotype, surgery rates, type of surgery, perianal fistulizing disease, and extraintestinal manifestations.…”
Section: ) a Mo N G A L L I B D P A T I E N T S I N P A T I E N Tmentioning
confidence: 99%